The Effectiveness of Communication Strategies in Learning - Wafa, Mohammad Ali; Chamariyah, Chamariyah (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This study aims to help educators, particularly teachers at An Nur Kodak Sampang Islamic Middle School, implement effective learning communication strategies. By applying the right communication methods, the learning process can have a positive impact, especially in motivating students and increasing their interest in learning. Effective communication between teachers and students is essential to ensure that information is clearly delivered and understood by students. The research focuses on finding the most appropriate communication strategy for teaching, allowing teachers to foster a dynamic, interactive learning environment. One of the study’s goals is to increase student motivation, which plays a crucial role in students’ commitment to the learning process. Higher motivation and interest will drive active participation and improve students' understanding of the material. Using a qualitative descriptive approach, the study gathers data from interviews, direct observations, and relevant documents, providing a holistic view of the teaching dynamics. The study also explores various factors that can hinder effective communication, such as environmental distractions and language limitations, offering solutions for teachers to overcome these barriers. By improving teacher communication skills and addressing these obstacles, the research aims to enhance the quality of learning and create a more conducive environment for students at An-Nur Kodak Sampang Islamic Middle School.